Penerapan Aplikasi E-Learning dan Akun Belajar.id dalam Meningkatkan Kualitas Pembelajaran di Sekolah - Tia Mugi Winasih; Ali Mas’ud; Nabil Wafa Athullah; Nur Fuadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to examine the application of e-learning applications and the Belajar.id account in improving the quality of learning in schools. This research uses a qualitative method with a descriptive approach. Data was collected through observation, interviews and documentation. The research subjects were teachers and students at schools who had implemented e-learning applications and Belajar.id accounts. The research results show that the implementation of e-learning applications and the Belajar.id account has a positive impact on the quality of learning. This is demonstrated through increased student learning motivation, accessibility of learning materials and more effective teacher-student interactions. However, this research also found several obstacles, such as a lack of internet access in some areas and a lack of training for teachers in using e-learning applications. This research recommends that schools continue to support the development of technological infrastructure and provide adequate training for teachers to maximize the use of e-learning applications and Belajar.id accounts in improving the quality of learning.